Estimation and validation of spatio-temporal parameters for sprint running using a radio-based tracking system. (8th December 2017) - Seidl, Thomas; Linke, Daniel; Lames, Martin
Abstract: Spatio-temporal parameters like step length, step frequency and ground contact time are directly related to sprinting performance. There is still a lack of knowledge, however, on how these parameters interact. Recently, various algorithms for the automatic detection of step parameters during sprint running have been presented which have been based on data from motion capture systems, video cameras, opto-electronic systems or Inertial measurement units. However, all of these methods suffer from at least one of the following shortcomings: they are (a) not applicable for more than one sprinter simultaneously, (b) only capable of capturing a small volume or (c) do not provide accurate spatial parameters. To circumvent these issues, the radio-based local position measurement system RedFIR could be used to obtain spatio-temporal information during sprinting based on lightweight transmitters attached to the athletes. To assess and optimize the accuracy of these parameters 19 100 m sprints of twelve young elite athletes (age: 16.5 ± 2.3 years) were recorded by a radio-based tracking system and a opto-electronic reference instrument. Optimal filter parameters for the step detection algorithm were obtained based on RMSE differences between estimates and reference values on an unseen test set. Attaching a transmitter above the ankle showed the best results. Bland-Altman analysis yielded 95% limits of agreement of [−14.65 cm, 15.05 cm] for step length [−0.016 s, 0.016 s] for step time and [−0.020 s, 0.028 s] for ground contact time, respectively. RMS errors smaller than 2% for step length and step time show the applicability of radio-based tracking systems to provide spatio-temporal parameters. This creates new opportunities for performance analysis that can be applied for any running discipline taking place within a stadium. Since analysis for multiple athletes is available in real-time this allows immediate feedback to coaches, athletes and media.